Both the scion and rootstock of grafted grapevines influence the rhizosphere and root endophyte microbiomes, but rootstocks have a greater impact - Lailheugue, Vincent; Darriaut, Romain; Tran, Joseph; Morel, Marine; Marguerit, Elisa; Lauvergeat, Virginie (Environmental microbiome, 2024)
Background Soil microorganisms play an extensive role in the biogeochemical cycles providing the nutrients necessary for plant growth. Root-associated bacteria and fungi, originated from soil, are also known to influence host health. In response to environmental stresses, the plant roots exude specific molecules influencing the composition and functioning of the rhizospheric and root microbiomes. This response is host genotype-dependent and is affected by the soil microbiological and chemical properties. It is essential to unravel the influence of grapevine rootstock and scion genotypes on the composition of this microbiome, and to investigate this relationship with plant growth and adaptation to its environment. Here, the composition and the predicted functions of the microbiome of the root system were studied using metabarcoding on ten grapevine scion-rootstock combinations, in addition to plant growth and nutrition measurements. Results The rootstock genotype significantly influenced the diversity and the structure of the bacterial and fungal microbiome, as well as its predicted functioning in rhizosphere and root compartments when grafted with the same scion cultivar. Based on β-diversity analyses, 1103P rootstock showed distinct bacterial and fungal communities compared to the five others (RGM, SO4, 41B, 3309 C and Nemadex). The influence of the scion genotype was more variable depending on the community and the investigated compartment. Its contribution was primarily observed on the β-diversity measured for bacteria and fungi in both root system compartments, as well as for the arbuscular mycorrhizal fungi (AMF) in the rhizosphere. Significant correlations were established between microbial variables and the plant phenotype, as well as with the plant mineral status measured in the petioles and the roots. Conclusion These results shed light on the capacity of grapevine rootstock and scion genotypes to recruit different functional communities of microorganisms, which affect host growth and adaptation to the environment. Selecting rootstocks capable of associating with positive symbiotic microorganisms is an adaptation tool that can facilitate the move towards sustainable viticulture and help cope with environmental constraints.